The Clover: herbal soap guidance system for product commercialization - Che Hassan, Nur Fairuz Aliah; Mat Isa, Farhana; Yacob, Yusma Amirah (University Community Transformation Centre, Universiti Putra Malaysia, 2017)
The Clover is an Herbal Soap Guidance System that specially made for the supplier of herbal soap product to commercialize their product. The Clover make a platform for the supplier to gives information about their product in the system. The supplier also can be located at the address or contact number provided in the system. The supplier also has their own account in this system and they will be the administrator of the system. They also can edit the product based on their stock. The Clover also gives the customer opportunities to communicate with the suppliers in the review page. They can comment and also get the product from this system. Hence, the customer will not be worried about being cheated by the supplier because they can locate the supplier.